Distinção em 140 caracteres: classe social, telenovela e twitter - Depexe, Sandra Dalcul (2015)
This thesis has the overall goal of exploring the circulation and consumption of the telenovela Salve Jorge (Rede Globo, 2012/2013) on Twitter to understand the phenomenon of TVInternet simultaneous consumption and the functioning of the word periguete in communication and class distinction. The specific objectives include: a) examine the real conditions, on Twitter, in which they develop the circulation and consumption practices in the context of media convergence; b) identify in the circulation of Salve Jorge the multiple forms of interactivity and participation of the subjects; c) understand how the social classes shapes the way-subject periguete , from the empirical indicators like as clothing, personal relationships and the way of life of the characters of Salve Jorge read as part of the circulation and consumption based on comments on Twitter. Therefore, we articulate the Pêcheux s speech analysis, Bourdieu s sociology and Latin American reception/consumption studies. We used methods and techniques coming from Social Network Analysis (SNA) and social media monitoring and operationalized through computer assisted qualitative analysis (CAQDAS - Computer Aided Qualitative Data Analisys Softwares). In our concerns stand out the speeches - from the telenovela and from the audience - that differentiate the female characters according to the social class they represent. To perform the analysis, we selected three trajectories of characters from Salve Jorge and seek them to describe how the tweets were constructed, indicating the evidences that pointed us to the forms-subjects that determine women as periguete . Disconnected from marriage and motherhood, these characters are fleeing from an traditional woman construction and approache of contemporary female models. As a result, form-subject periguete functions as a subject position, whose senses are dynamic, but refer to women s freedom with her body, like in the way they dresses and make beauty treatments, either in the exercise of their sexuality. The dynamic of these senses is for judgment/acceptance of popular class women and reproof/freedom of upper classes women, in what regards to the uses of their bodies.